Comparative efficacy of teclistamab versus physician's choice of therapy in the long-term follow-up of APOLLO, POLLUX, CASTOR, and EQUULEUS clinical trials in patients with triple-class exposed relapsed or refractory multiple myeloma - Mateos, Maria-Victoria; Chari, Ajai; Usmani, Saad Z.; Goldschmidt, Hartmut; Weisel, Katja; Qi, Keqin; Londhe, Anil; Nair, Sandhya; Lin, Xiwu; Pei, Lixia; Ammann, Eric; Kobos, Rachel; et al. (Clinical lymphoma, myeloma & leukemia, 2023)
Background - The efficacy and safety of teclistamab in patients with RRMM who received ≥3 prior lines of therapy and were triple-class exposed (TCE) are being evaluated in the single-arm, multicohort, phase I/II MajesTEC-1 trial (NCT04557098). We evaluated the comparative effectiveness of teclistamab versus physician's choice (PC) of therapy in TCE RRMM patients. - Methods - Individual patient-level data from MajesTEC-1 patients who received teclistamab (1.5 mg/kg weekly; clinical cutoff March 16, 2022) were included. An external control arm was created from patients in long-term follow-up of 4 clinical trials of daratumumab who were treated with PC therapy after discontinuation of trial treatments. In the primary analysis, inverse probability of treatment weighting was used to adjust for imbalances in 9 baseline covariates. A fully adjusted model included 5 additional prognostic factors. Outcomes included overall response rate (ORR), very good partial response or better (≥VGPR) rate, overall survival (OS), progression-free survival (PFS), and time to next treatment (TTNT). - Results - After adjustment, baseline characteristics were balanced between cohorts. In the primary analysis, outcomes were significantly improved with teclistamab versus PC: ORR (OR [95% CI] 4.81 [3.04-7.72]; P < .0001); ≥VGPR rate (OR, 12.07 [6.91-22.11]; P < .0001); OS (HR, 0.54 [0.40-0.73]; P < .0001); PFS (HR, 0.59 [0.46-0.78]; P = .0001); and TTNT (HR, 0.32 [0.24-0.42]; P < .0001). Results of the fully adjusted model were consistent with the primary analysis. - Conclusion - Teclistamab showed significantly improved effectiveness versus PC on all outcomes, highlighting its clinical benefit in patients with TCE RRMM and limited treatment options.